Selecting conservation reserves using species covering models: Adapting the ARC/INFO GIS - Gerrard, R. A.; Church, R. L.; Stoms, D. M.; Davis, F. W. (Transactions in GIS, 1997)
Conflicts between human development of the landscape and conservation of biodiversity will continue to grow. Given this reality, there have been a number of attempts to model the optimal selection of conservation reserve sites such that maximum biodiversity protection can be attained within a limited budget for land acquisition. Here we adapt the Location-Allocation module of ARC/INFO to solve the problem of representing, or covering, as many species as possible in a fixed number of selected reserve sites. Resident ARC/INFO solution routines are applied to an innovative logical network that converts the problem of optimal reserve selection into a problem of optimal facility placement, which the Location-Allocation module can recognize and solve. Use of this unique logical network structure as input to ARC/INFO's internal solvers makes possible, compared to previous methods, a much tighter integration of spatial optimization tools with mapping and database tools, all of which are internal to the GIS and accessed via a menu-driven interface. The main advantage is that users of public domain data (such as the U.S. Gap Analysis data) can conduct their own explorations of possible reserve systems without having to acquire and master optimization packages and reformat model output data for GIS display and post-analysis of solutions. Our sample application uses species data from southwestern California. We also present a second major form of species covering model grounded in the same logical network. This enhanced model accommodates weighting of species by their conservation importance, thus allowing reserve systems to be designed around the portection of the most threatened or vulnerable biota.